THE EDUCATIONAL VALUE OF MUSIC CLUBS (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the importance of creating music clubs in general education schools, effective methods and the influence of students on creative development, as well as Five important initiatives aimed at increasing students' interest in art in general education schools, identifying their talents and effective leisure activities, creating clubs of Uzbek musical folklore and performing on national instruments. The ways of educating the generation in the spirit of national values are highlighted.